2019
DOI: 10.1021/acs.orglett.9b02142
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-Catalyzed Phthalide Synthesis from Benzamides and Aldehydes via C–H Bond Activation

Abstract: The [4 + 1] annulation of benzamides and aldehydes for phthalide synthesis was achieved via rhenium-catalyzed C–H activation, which demonstrates an unprecedented reaction pattern distinct from those of other transition-metal catalyses. The reaction also features readily available starting materials, a wide scope for both electro-rich and electro-deficient substrates, and the elimination of homoannulation byproducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…According to above observations and previous reported studies, [ 14–22 ] a plausible catalytic cycle is proposed (Scheme 5). First, [RuCl 2 ( p ‐cymene)] 2 is converted by AgSbF 6 to the catalytically active ruthenium species I , which reacts with amide 1 to generate a five‐membered ruthenium intermediate II through chelate directed C–H activation.…”
Section: Figuresupporting
confidence: 58%
See 1 more Smart Citation
“…According to above observations and previous reported studies, [ 14–22 ] a plausible catalytic cycle is proposed (Scheme 5). First, [RuCl 2 ( p ‐cymene)] 2 is converted by AgSbF 6 to the catalytically active ruthenium species I , which reacts with amide 1 to generate a five‐membered ruthenium intermediate II through chelate directed C–H activation.…”
Section: Figuresupporting
confidence: 58%
“…Our study was intrigued by a previously reported procedure for the synthesis of 3‐unsubstituted phthalides from benzamides by Faigl, Volk and co‐workers, [ 13 ] involving ortho ‐lithiation, formylation, reduction and lactonization processes (Scheme 1c). Encouraged by the advances in the ortho ‐hydroxymethylation with paraformaldehyde via transition metal catalyzed C–H activation (e.g., ruthenium catalysis by Zhou, [ 14 ] Ding, [ 15 ] Wu, [ 16 ] and Kim [ 17 ] with pyridyl or pyrimidinyl as the directing group, rhodium catalysis by Kim [ 18 ] with azobenzene as substrate, manganese catalysis by Glorius [ 19 ] with pyridyl or pyrimidinyl as the directing group, cobalt‐catalyzed hydroxymethylarylation of terpenes with formaldehyde and arenes by Chen [ 20 ] ) and recent progress in the synthesis of 3‐substituted phthalides from benzamides and aldehydes by rhenium‐ [ 21 ] and rhodium‐catalysis, [ 22 ] we proposed that it might be possible to prepare 3‐unsubstituted phthalides in a single step by a sequential transition‐metal‐catalyzed ortho ‐hydroxymethylation and intramolecular lactonization strategy.…”
Section: Figurementioning
confidence: 99%
“…We next investigated carbamates and tertiary amides, both classic ortho -directing groups, 1 as promoters of Wittig rearrangement, but this was uniformly unsuccessful. The diethylcarbamate 12 suffered a nucleophilic attack at carbonyl to give 13 and 14 in low yield while the phenylcarbamate 15 was recovered unchanged ( Scheme 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al described a rhenium-catalyzed phthalide synthesis from benzamides and aldehydes via C-H bond activation (Scheme 18). [36] The [4+1] annulation of benzamides and aldehydes for phthalide synthesis was achieved via rheniumcatalyzed C-H activation, which demonstrates an unprecedented reaction pattern distinct from those of other transition metal catalysts. The reaction also has characteristic readily available starting materials, a wide scope for both electro-rich and electro-deficient substrates, and the elimination of homoannulation byproducts.…”
Section: Benzamide Reacts With Aldehydes To Synthesize Phthalidementioning
confidence: 99%